Not All Past Events Are Equal: Biased Attention and Emerging Heuristics in Children's Past‐to‐Future Forecasting. Issue 6 (10th March 2013) - Lagattuta, Kristin Hansen; Sayfan, Liat
Abstract : Four‐ to 10‐year‐olds and adults ( N  = 265) responded to eight scenarios presented on an eye tracker. Each trial involved a character who encounters a perpetrator who had previously enacted positive (P), negative (N), or both types of actions toward him or her in varying sequences (NN, PP, PN, and NP). Participants predicted the character's thoughts about the likelihood of future events, emotion type and intensity, and decision to approach or avoid. All ages made more positive forecasts for PP > NP > PN > NN trials, with differentiation by past experience widening with age. Age‐related increases in weighting the most recent past event also appeared in eye gaze. Individual differences in biased visual attention correlated with verbal judgments. Findings contribute to research on risk assessment, person perception, and heuristics in judgment and decision making.